Cytotoxic activity of Ethyl-p-Methoxycinnamate from Kaempferia galanga in HSC-4 Oral Cancer Cells - Wastuti Hidayati Suriyah; Razak Kasmuri, Abdul; Lokman Md. Isa, Muhammad; J. A. Ichwan, Solachuddin (Lembaga Penelitian Universitas YARSI, 2024)
Abstract Introduction: Oral cancer is a prevalent malignancy associated with high mortality and morbidity, primarily due to its poor prognosis. Recently, phytomedicines have attracted interest for their potential role in chemotherapy. Kaempferia galanga, a medicinal herb, has shown anticancer properties in various human cancer cell lines, mainly due to its active compound, ethyl-p-methoxycinnamate (EPMC). Objective: This in vitro study aimed to assess the cytotoxic effects of EPMC on the HSC-4 oral cancer cell line. Materials and Methods: HSC-4 cells were treated with various concentrations of EPMC for 24 hours, and cytotoxicity was measured using the MTT assay. Results: EPMC exhibited dose-dependent cytotoxicity, with an IC50 value of 0.032 mg/mL. Discussion: These findings suggest that EPMC is a promising anticancer agent. Further research should investigate its molecular mechanisms and potential as a chemosensitizer when combined with standard chemotherapeutic drugs. Conclusion: EPMC induces cytotoxicity in HSC-4 cells, positioning it as a promising candidate for further exploration in oral cancer treatment. Keywords: Cytotoxicity, EPMC, HSC-4, Oral Cancer